2014
DOI: 10.1186/1471-2164-15-889
|View full text |Cite
|
Sign up to set email alerts
|

Impact of whole-genome amplification on the reliability of pre-transfer cattle embryo breeding value estimates

Abstract: BackgroundGenome-wide profiling of single-nucleotide polymorphisms is receiving increasing attention as a method of pre-implantation genetic diagnosis in humans and of commercial genotyping of pre-transfer embryos in cattle. However, the very small quantity of genomic DNA in biopsy material from early embryos poses daunting technical challenges. A reliable whole-genome amplification (WGA) procedure would greatly facilitate the procedure.ResultsSeveral PCR-based and non-PCR based WGA technologies, namely multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…Preimplantation genomic selection in cattle based on SNP genotypes is receiving increased attention as a means of accelerating genetic improvement by increasing selection pressure and avoiding the cost of producing genetically inferior animals [6, 19,20,21]. Although several groups have reported the potential of preimplantation genomic selection in dairy cattle [10, 11, 22,23,24], studies in Japanese Black cattle using this technique are limited. In the present study, we investigated the accuracy of GEBVs for carcass traits in preimplantation embryos derived from Japanese Black cattle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preimplantation genomic selection in cattle based on SNP genotypes is receiving increased attention as a means of accelerating genetic improvement by increasing selection pressure and avoiding the cost of producing genetically inferior animals [6, 19,20,21]. Although several groups have reported the potential of preimplantation genomic selection in dairy cattle [10, 11, 22,23,24], studies in Japanese Black cattle using this technique are limited. In the present study, we investigated the accuracy of GEBVs for carcass traits in preimplantation embryos derived from Japanese Black cattle.…”
Section: Discussionmentioning
confidence: 99%
“…[10] explored suitable WGA methodologies for SNP genotyping using biopsied embryonic cells (approximately 15 cells), and indicated that the illustra GenomiPhi V2 DNA amplification kit (GE Healthcare, MDA based method) produced the best results. Indeed, regarding the genetic value of the Lifetime Profit Index, their results showed an extremely high correlation (r = 0.99) between biopsied embryonic cells and the corresponding post-natal calves using the kit [10]. Correspondingly, we chose the illustra Single Cell GenomiPhi DNA Amplification Kit (GE Healthcare) for WGA in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also proposed in vitro culture of biopsied cells as a means of increasing the amount of DNA template and the reliability of genotyping. However, another researcher indicated that the cell culture approach is unacceptable from a commercial point of view because larger biopsies (20 to 30 cells) were required for successful cell proliferation in culture, leading to significant reduction in embryo viability [ 20 ]. The use of elongating conceptuses allows a large number of cells to be biopsied without any reduction in viability; therefore, we attempted to develop a genomic selection system by PGD combined with the elongating conceptus transfer technique.…”
Section: Discussionmentioning
confidence: 99%
“…While it is possible to collect embryo biopsies for DNA genotyping without affecting the pregnancy rate of the embryos (Saadi et al, 2014), the IVP-ET efficiency is still relatively low and remains the bottleneck in this process. A possible way to increase the efficiency of IVP-ET procedures is identification and selection of high-quality oocyte donors and embryo recipients.…”
Section: Introductionmentioning
confidence: 99%